B Cell Intrinsic STING Signaling Is Not Required for Autoreactive Germinal Center Participation - Green, Kenneth; Wittenborn, Thomas R.; Fahlquist-Hagert, Cecilia; Terczynska-Dyla, Ewa; van Campen, Nina; Jensen, Lisbeth; Reinert, Line; Hartmann, Rune; Paludan, Søren R.; Degn, Søren E. (Frontiers in Immunology, 2021)
Germinal centers (GCs) are induced microanatomical structures wherein B cells undergo affinity maturation to improve the quality of the antibody response. Although GCs are crucial to appropriate humoral responses to infectious challenges and vaccines, many questions remain about the molecular signals driving B cell participation in GC responses. The cyclic GMP-AMP synthase (cGAS)-stimulator of interferon genes (STING) pathway is an important mediator of type I interferon and proinflammatory cytokine responses during infection and cellular stress. Recent studies have reported important roles for STING in B cell responses, including an impact on GC B cells and downstream antibody responses, which could have great consequences for vaccine design and understanding STING-associated interferonopathies. GCs are also involved in untoward reactions to autoantigens in a plethora of autoimmune disorders, and it is generally thought that these responses coopt the mechanisms used in foreign antigen-directed GCs. Here, we set out to investigate the importance of the cGAS-STING pathway in autoreactive B cell responses. In a direct competition scenario in a murine mixed bone marrow chimera model of autoreactive GCs, we find that B cell intrinsic deficiency of cGAS, STING, or the type I interferon receptor IFNAR, does not impair GC participation, whereas Toll-like receptor (TLR)-7 deficiency mediates a near-complete block. Our findings suggest that physiological B cell responses are strictly sustained by signals linked to BCR-mediated endocytosis. This wiring of B cell signals may enable appropriate antibody responses, while at the same time restricting aberrant antibody responses during infections and in autoimmune or autoinflammatory settings.